0032 Physical capacity in midlife and labour market attachment among older workers: prospective cohort study with register follow-up. (21st August 2017) - Sundstrup, Emil; Hansen, Åse Marie; Mortensen, Erik Lykke; Poulsen, Otto; Clausen, Thomas; Rugulies, Reiner; Møller, Anne; Andersen, Lars
Abstract : Introduction: We aim to determine the prospective association of different physical capacity tests with health related labour market outcomes among older workers. Methods: The prospective risk of register-based long-term sickness absence (LTSA) and disability pension from measured musculoskeletal capacity (jump performance, postural balance, sit-to-stand, explosive muscle strength, and maximal strength of the hand, back and abdominal muscles) and cardiovascular capacity (lung function and aerobic fitness) were estimated among 5076 older workers from the Copenhagen Ageing and Midlife Biobank. Time-to-event analyses were censored for competing events and adjusted for age, gender, physical and psychosocial work environment, lifestyle, socioeconomic position and previous LTSA. Results: Low physical capacity in many of the tests (less than 1SD below mean) predicted risk of LTSA and disability pension. Specifically, low aerobic fitness (HR 5.9), low jump performance (HR 2.7) and low abdominal muscle strength (HR 3.3) predicted risk of disability pension. A dose-response association was observed between number of musculoskeletal capacity tests with low performance and disability pension and LTSA - with the risk-estimate for disability pension being 7.6 when low capacity was present in ≥5 musculoskeletal capacity tests. Population attributable risks for disability pension and LTSA from poor musculoskeletal capacity were 33% and 8%, respectively. Conclusions: Poor musculoskeletal and cardiovascular capacity in midlife increased the risk for LTSA and disability pension. Promoting physical capability to a normal level among older workers with low capacity may have the opportunity to prevent premature exit from the labour market.